2003
DOI: 10.1038/sj.npp.1300258
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography Studies of Potential Mechanisms Underlying Phencyclidine-Induced Alterations in Striatal Dopamine

Abstract: Positron emission tomography (PET), in combination with 11 C-raclopride, was used to examine the effects of phencyclidine (PCP) on dopamine (DA) in the primate striatum. In addition, we explored the hypotheses that GABAergic pathways as well as molecular targets beyond the N-methyl-D-aspartate (NMDA) receptor complex (ie dopamine transporter proteins, DAT) contribute to PCP's effects. In the first series of experiments, 11 C-raclopride was administered at baseline and 30 min following intravenous PCP administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…Only three imaging studies reported separate estimations of dorsal and ventral striatal binding. Among the positive studies, neither Vollenweider, nor Schiffer found greater effects on ventral striatal as opposed to the dorsal striatal binding (Vollenweider et al, 2000;Schiffer et al, 2003), while the negative study by Kegeles reports a similar lack of regional effects (Kegeles et al, 2002). Third, recent reports indicate that neither ketamine nor PCP is selective for the NMDA site.…”
Section: Are Any Observed Decreases In Radioligand Binding a Consequementioning
confidence: 92%
See 1 more Smart Citation
“…Only three imaging studies reported separate estimations of dorsal and ventral striatal binding. Among the positive studies, neither Vollenweider, nor Schiffer found greater effects on ventral striatal as opposed to the dorsal striatal binding (Vollenweider et al, 2000;Schiffer et al, 2003), while the negative study by Kegeles reports a similar lack of regional effects (Kegeles et al, 2002). Third, recent reports indicate that neither ketamine nor PCP is selective for the NMDA site.…”
Section: Are Any Observed Decreases In Radioligand Binding a Consequementioning
confidence: 92%
“…Notwithstanding this, there is no obvious relationship between the dose of ketamine and a significant change in imaging parameters. In a single study using phencyclidine (PCP), a significant change in 11 C-raclopride BP was seen, however it was not dose dependent, being present at 0.5 mg/kg Ϫ1 , but not at 0.1 mg/kg Ϫ1 or 1 mg/kg Ϫ1 (Schiffer et al, 2003).…”
Section: Effects Of Dosementioning
confidence: 97%
“…Infusion of NMDA into striatum in intact animals increases both DA and GABA release (Hernandez et al, 2003), consistent with this model. Further, GABAergic inhibitory mechanisms in striatum have been demonstrated in both rodent (Hanania and Johnson, 1999;Hernandez et al, 2003) and primate (Schiffer et al, 2003) striatum, demonstrating in vivo relevance of this pathway to intrinsic DA regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Their actions are variably attenuated by antipsychotics such as haloperidol and clozapine (Malhotra et al 1997;Lahti et al 2001;Oranje et al 2002, Van Berckel 2003. Neuronal mechanisms underlying the effects of OCBs are many, of which the following should be briefly evoked: 1) Sensitisation of subcortical and cortical dopaminergic pathways (Kegeles et al 2000(Kegeles et al , 2002Balla et al 2003;Laruelle et al 2003) 2) Activation of mesolimbic serotonergic pathways and consequent recruitment of corticolimbic populations of 5-HT 2A receptors, effected independents of NMDA receptors One common mechanism underlying these changes may be interruption of a NMDA receptor-mediated, tonic excitation of GABAergic interneurones inhibitory to projection neurones (Carlsson et al 2001;Farber 2003;Schiffer et al 2003;Shi and Zhang 2003;de Lima et al 2004). Underpinning a role of NMDA receptors in the psychotomimetic effects of PCP and ketamine in man and rodents, they are at least partially mimicked by antagonists at the NMDA recognition site (Lowe et al 1994;Muir and Lees 1995;Bakshi et al 1999;Dyker et al 1999).…”
Section: Pro-psychotic Actions Of Open Channel Blockersmentioning
confidence: 98%